Monitoring Employee Behavior Through the Use of Technology and Issues of Employee Privacy in America. (13th April 2015) - Moussa, Mahmoud
Despite the historic American love for privacy that has enhanced innovation and creativity throughout the country, encroachments on privacy restrain individual freedom. Noticeable, advances in technology have offered decision makers remarkable monitoring aptitudes that can be used in numerous tasks for multiple reasons. This has led scholars and practitioners to pose a significant number of questions about what is legitimate and illegitimate in the day-to-day affairs of a business. This article is composed of (a) research about electronic monitoring and privacy concerns; (b) definitions of, critiques of, and alternatives to electronic performance monitoring (EPM); (c) motives behind employee monitoring and leadership behaviors; (d) advice that makes monitoring less distressful; (e) employee monitoring policies; (f) reviewing policies and procedures; (g) the role of human resource development (HRD) in employee assessment and development; and (h) conclusion and recommendations for further studies.